NMR evaluation of stroke in the rat. - Bryan, R N; Willcott, M R; Schneiders, N J; Rose, J E (American Journal of Neuroradiology, 1983)
Cortical stroke was produced in rats by cautery occlusion of the middle cerebral artery distal to the lenticulostriate origins. Brains were removed, and nuclear magnetic resonance (NMR) scans of whole fixed brains and in vitro measurements of small samples were obtained. Brain tissue was then processed for histology. Routine scans used a modified spin-echo technique. Spin-density and T2-dependent scans were also obtained. Infarcts were detectable in 6 hr due to diminution of the spin-echo intensity from T2 prolongation. NMR changes increased gradually over 48 hr and coincided anatomically with evidence from the neuropathologic sections. NMR imaging is a very sensitive method of evaluating acute cerebral infarction in this animal model.